Pelatihan Pengelolaan Minyak Jelantah Sebagai Upaya dalam Menumbuhkan Masyarakat Berwirausaha - Nurul Alfian; Rohmaniyah Rohmaniyah; Rika Syahadatina; Nur Syakherul Habibi (Universitas Maritim AMNI Semarang, 2025)
Used cooking oil is used cooking oil which is often considered waste and thrown away without proper processing. Uncontrolled disposal of used cooking oil can cause various environmental problems, such as soil and water pollution. For the environment, used cooking oil can have a serious impact because it pollutes the stability of soil and water when the waste is not managed carefully. Used cooking oil is included in non-hazardous and toxic waste but must receive proper handling so as not to cause environmental damage. On the other hand, used cooking oil has the potential to be processed into products of economic value, such as soap, candles, or biodiesel. The implementation of this service is carried out by providing outreach to the community regarding the processing of used cooking oil into economic goods that can be reused by the community. Processing used cooking oil into candles and soap could be a solution to improve the community's economy, knowledge, and skills, as well as interest in producing soap and candles from processed used cooking oil which is easy to process and become a benchmark for the success of the training in motivating the Ceguk village community to entrepreneurship.